Association between sleep quality and obesity in adolescents - Nova Juliana Sagala; Sri Sofyani; Supriatmo Supriatmo (Paediatrica Indonesiana, 2017)
Background Sleep quality can be measured by the Pittsburgh Sleep Quality Index (PSQI). One component of the PSQI is duration of sleep, which is often highly inadequate in adolescents. Inadequate sleep may lead to obesity in adolescents.Objective To assess for an association between sleep quality and incidence of obesity in adolescents.Methods This case–control study was conducted at Santo Thomas I Senior High School, Medan, North Sumatera, from July to August 2015. A total of 227 adolescents were divided into two groups: the case group consisting of 101 obese adolescents and the control group consisting of 126 non-obese adolescents. Study data was collected by questionnaires and PSQI. We interviewed subjects on their food consumption for the three days prior and calculated their average caloric intake. The data were analyzed by non-paired T-test, Chi-square, Mann-Whitney, and multivariate analyses.Results There was a significant association between sleep quality and obesity [OR 3.87 (95%CI 1.920 to 7.829)]. Median PSQI (range) score in the obese group was significantly higher than in the non-obese group [6.00 (2-16) vs. 5.00 (2-12), respectively (P=0.0001)]. In addition, sleep latency (P=0.002) and sleep duration (P=0.0001) were significantly different between groups. Multivariate analysis revealed a significant association between poor sleep quality and high caloric intake.Conclusion Sleep duration in obese adolescents is significantly shorter than that in non-obese adolescents. In addition, sleep latency in obese adolescents was significantly longer than that in non-obese adolescents.